A study on the significance of ethnicity to child undernutrition in the Philippines - Eiman, Alyza Hope (Animo Repository, 2021)
Child undernutrition is one of the most prevalent issues researched in many countries including the Philippines, as the three faces of child undernutrition such as stunting, wasting and underweight is closely associated with most of the indigenous families in the country. As such, this study aimed to determine whether ethnicity significantly affects child undernutrition in the Philippines for children ages 0 to 5 years old in 2013 and 2015 and compare the changes in child undernutrition. A set of data from the National Nutrition Surveys conducted by FNRI in 2013 and 2015 has been analyzed separately using OLS method and the result showed that ethnicity among indigenous people is a significant contributor to the child's stunting, wasting, and undernutrition from age 5 and below. While it is notable that the values for stunting, wasting and underweight has slightly improved in 2015, the result in stunting is the only one that remained significant. The minimal improvement of the results from 2013 to 2015 could be further addressed by more government programs concerning the health of indigenous persons in the Philippines.